Case Study on the Impact of Workload, Motivation, and Discipline on Employee Performance at PT. Caturkarda Depo Bangunan, Tbk - Bancin, Modesta; Susilo, Sophia Reni; Anatasia, Velly (Universitas Bunda Mulia, 2025)
This study investigates the impact of workload, work motivation, and work discipline on employee performance within the receiving division of PT. Caturkarda Depo Bangunan Tbk, a building materials retailer in Indonesia. A significant decline in this division's performance, from